A New bis(rhodamine)-Based Fluorescent Chemosensor for Fe(3+) - Chen, Xiaopo (Springer US, 2011)
A new bis(rhodamine)-based fluorescent probe 4 was synthesized, and it exhibited high selectivity for Fe(3+) over other commonly coexistent metal ions in both 50% ethanol and Tris–HCl buffer. Upon the addition of Fe(3+), the spirocyclic ring of 4 was opened and a significant enhancement of visible color and fluorescence in the range of 500–600 nm was observed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10895-011-1022-0) contains supplementary material, which is available to authorized users.